AAGC-Autonomous Armed Guard Companion - Deepak, D; Dinesh Kumar, A; Gokulakrishna, M (International Journal of Engineering and Technology, 2018)
Technology has revolutionized human world over the past centuries. The world has started to move towards the autonomous world. However, in terms of security and safety of humans from antisocial threat person, technology has not achieved its peak in providing autonomous system. Places such as airport, railways stations, and malls are well secured either by metal detectors or by manual scrutiny. Moreover, the current scenario demands a very high security in common places such as hospital, schools, and community halls where manual security checks might not be possible. In this work an autonomous system is developed to detect and track concealed weapons with potential to stop the threat person before causing any harm or danger. The system achieves its task by carrying out three main functions in a sequential order. A microwave sensor and metal detector together detects the concealed weapon by means of the Doppler shift in the radiation and eddy currents induced in the metal respectively. Secondly, the output voltage from the microwave senor is processed by a microcontroller. Lastly, a DC motor attached with a laser pointer, receives input from microcontroller such that rotates in a direction pointing the concealed weapon.Â Â